Effect of Cucurbita pepo (Pumpkin) seed extracts on the cyclicity and reproductive hormones of female Wistar rats - Chinwe Fiona Anyanwu; Owunari Abraham Georgewill; Udeme Owunari Georgewill (Journal of HerbMed Pharmacology)
Introduction: Despite the traditional use of Cucurbita pepo seed in pregnancy, its effects on female reproduction remain scarce. This study evaluated the impacts of n-hexane, dichloromethane (DCM), and aqueous ethanol extracts of C. pepo seed on the cyclicity and reproductive hormones of female Wistar rats. Methods: Ten groups of four rats received seed extracts or tween 80 orally for 21 days: A (control)= 0.5 mL tween 80 (vehicle); B, C, & D= 142.86, 285.71, and 428.57 mg/kg nHE; E, F, & G= 142.86, 285.71, 428.57 mg/kg of DCM; and H, I, & J= 142.86, 285.71, 428.57 mg/kg of aqueous ethanol extracts, respectively. Vaginal cytology monitored the estrous cycle daily, and blood samples were obtained for follicle-stimulating hormone (FSH), luteinizing hormone (LH), estrogen, and progesterone at various oestrus cycle phases. Results: Compared to the control, the estrous cycle phases did not change significantly (P>0.05). FSH levels significantly increased (P<0.05) with DCM and aqueous ethanol extracts of C. pepo seed during proestrus and estrus phases compared to the control. A significant (P<0.05) increase in LH was observed with n-hexane, DCM, and aqueous ethanol extracts during all estrous cycle phases compared to the control. All extracts significantly increased estrogen levels (P<0.05) during all phases. DCM and aqueous ethanol extracts reduced substantially the estrus-phase progesterone. Conclusion: Cucurbita pepo may stimulate the hypothalamic-pituitary-gonadal axis in female reproduction. Further studies should be conducted using various phytoestrogen compounds to gain useful knowledge about the effectiveness, safety, and long-term effects of C. pepo seed extracts in regulating hormonal balance.